Evaluating Egypt's renewable energy and energy subsidies policies. - El-Refai, Mahmoud Lotfy (AUC Knowledge Fountain, 2015)
Egypt and the Middle East region as a whole have the lowest domestic prices worldwide for primary energy and electricity which has resulted in an economic disincentive for investments in renewable energy leading to an underestimation of the true potential of renewable energy due to the absence of commercial incentives for investors. In order to unleash the renewable energy potential in Egypt, it is crucial to reconsider the domestic pricing framework, energy subsidies and restructuring the energy market where the economic advantages of renewable energy become clear. In 2008, the New and Renewable Authority (NREA) announced its goal of reaching a 20 % share of renewable energy in Egypt’s overall energy mix for electricity generation, an estimated 7200 MW. Today, almost a decade after setting this ambitious goal, the installed capacity of renewable energy in Egypt has reached a mere 550 MW. This research evaluates the development of Egypt’s renewable energy sector and its regulatory policies and draws lessons from the examples of other countries and the policies they adopted to foster the developed of the renewable energy sector. The transition to a wide adoption of renewable energy in Egypt would be slow, if left entirely to market forces due to the considerably high cost of electricity generated from renewable energy sources especially when compared to conventional generation which is heavily subsided by the government. The Egyptian government has a key role to play in order to accelerate the process by implementing the required policies to encourage renewable energy deployment on both the supply-side and demand-side. As Egypt starts to liberalize its energy market by removing energy subsidies to ease the pressure on the national budget, the research reviews Egypt’s energy subsidy systems and highlights the failures and successes of countries which have undergone a similar transition and concludes with recommendations for Egypt’s energy reality. The Egyptian government has taken the first steps in the right direction by gradually removing the energy subsidies and launching the Feed-in Tariff scheme thus allowing the private sector to develop renewable energy projects. It is recommended for Egypt to adopt a pricing scheme based on the actual incurred cost as it will eliminate inefficiencies and support the transition to renewable energy. In addition, the adoption of cash transfers instead of subsidies will result in a decrease in the over subsidies bill while increasing the efficient targeting of the poor.